2014
DOI: 10.1097/mpa.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Function of Islets Encapsulated in a Redesigned Alginate Microcapsule Construct in Omentum Pouches of Immune-Competent Diabetic Rats

Abstract: Objectives Our study aim was to determine encapsulated islet graft viability in an omentum pouch and the effect of FGF-1 released from our redesigned alginate microcapsules on the function of the graft. Methods Isolated rat islets were encapsulated in an inner core made with 1.5% low-viscosity high-mannuronic acid (LVM) alginate followed by an external layer made with 1.25% low-viscosity high-guluronic acid (LVG) alginate with or without FGF-1, in microcapsules measuring 300 – 400 μm in diameter. The two alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 44 publications
0
45
0
1
Order By: Relevance
“…The 0.5 μg aFGF group received a 100 μL aFGF‐loaded liposome injection and the 1.0 μg aFGF group received 200 μL aFGF loaded liposomes. The concentrations were chosen because 0.5 μg aFGF was most effective in enhancing the tube formation and in previous studies concentrations of 0.5–1.0 μg aFGF showed to improve islet engraftment 36, 37. Efficacy of the 800 islet‐dose in sham‐injected scaffolds was compared with that of scaffold treated with liposomes containing either 0.5 or 1.0 μg aFGF.…”
Section: Resultsmentioning
confidence: 99%
“…The 0.5 μg aFGF group received a 100 μL aFGF‐loaded liposome injection and the 1.0 μg aFGF group received 200 μL aFGF loaded liposomes. The concentrations were chosen because 0.5 μg aFGF was most effective in enhancing the tube formation and in previous studies concentrations of 0.5–1.0 μg aFGF showed to improve islet engraftment 36, 37. Efficacy of the 800 islet‐dose in sham‐injected scaffolds was compared with that of scaffold treated with liposomes containing either 0.5 or 1.0 μg aFGF.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shahjalal et al and Kudva et al reported successful differentiation of human-derived iPSCs into insulin--producing cells without using xenogeneic products or viral transgenic vectors respectively [168]. However, Thatava et al suggested that translation of results observed in mice might face significant challenges before translation to humans when he reported that iPSCs isolated from T1D patients exhibited significant variations in their ability to differentiate into insulin-expressing islet-like cells [169]. …”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Pancreatic stem cells [160,161], hESCs [162][163][164], induced pluripotent stem cells (iPSCs) [165][166][167][168][169], mesenchymal [170][171][172][173][174] and adipose-derived stem cells (ADSCs) [175,176] have all been used to derive islet-like cell clusters or insulin-producing cells (IPCs) that are viable, express markers similar to terminally differentiated β-cells (Insulin, GLUT2) and are able to respond to a glucose challenge. These cells have all demonstrated good function after encapsulation within bioencapsulation devices and several in vivo studies have also been conducted.…”
Section: Recent Developments In Stem Cell Therapy For T1dmentioning
confidence: 99%
“…28 Low-viscosity high-mannuronic acid (LVM) alginate (20-200 mPas; Nova-Matrix, Sandvika, Norway) was dissolved in 1.5% Eagle's minimum essential medium (MEM; Sigma-Aldrich, St. Louis, MO). Poly-l-ornithine (PLO; 30-70 kDa, Sigma-Aldrich), sodium citrate (Sigma-Aldrich), ultrapurified low-viscosity high-guluronic acid (LVG) alginate (75-200 kDa, G/M ratio £1), and LVM alginate (75-200 kDa, G/M ratio ‡1.5; Nova-Matrix, Sandvika, Norway) were also prepared in MEM.…”
Section: Methodsmentioning
confidence: 99%
“…4,9,24 Histological and immunohistochemical methods are also frequently used but are invasive and destructive, do not allow for three dimensional (3D) assessment of the sample, often alter biomaterial structure, and require processing and staining techniques. 4,[24][25][26][27][28][29] There is a need for noninvasive imaging that allows for 3D assessment of the implanted grafts and local tissue response to monitor and predict long-term success of the transplant. The ideal imaging technique would not require exogenous contrast and be nondestructive.…”
mentioning
confidence: 99%